Taxonomy of the genus eragrostis (Eragrostis wolf.) in Mongolia - Buyantogtokh, Bolor; Nyamdorj, Saruul (Mongolian Journal of Botany, 2024)
Annual plants in the vegetation cover of desert steppe and desert zones play a significant role, and one of these is the genus Eragrostis. To address the taxonomic issues of this genus, a total of 147 herbarium sheets stored in the Plant Collection (UBA) and digital herbarium database of the Botanic Garden and Research Institute of the Academy of Sciences were utilized. In Mongolia, the placement of glands on vegetative and reproductive organs, the location of hairs on reproductive organs, the shape and size of spikelets, the number of flowers, and the shape and size of the lower glume are stable traits for species identification within the genus Eragrostis (Eragrostis Wolf). Based on these characteristics, four species of Eragrostis are identified as growing in Mongolia: Eragrostis minor Host., Eragrostis pilosa (L.) Beauv., Eragrostis amurensis Probat., and Eragrostis cilianensis (All.) Vignolo ex Janch. These species are distinguished by gland placement and shape along the leaf margins and lower surface, the number of flowers, the shape of spikelets, and the hairs at the joints of the awns. A species identification key was developed based on these traits. Eragrostis amurensis, which was not previously recorded in earlier literature, was found in the Khuvsgul, Khentii, Mongolian Dauria, Mongolian Altai, Central Khalkha, Eastern Mongolia, Olon Nuur, and Dornogovi regions. Meanwhile, Eragrostis minor was newly recorded in the meadow steppe of the Khentii Mountain region, and Eragrostis pilosa was newly documented in the desert steppe of Khovd region. Монгол орны хургалжийн (Eragrostis Wolf.) төрлийн ангилалзүй Хураангуй. Цөлийн хээр, цөлийн бүсийн ургамлан нөмрөгт нэг наст ургамлууд чухал ач холбогдтой бөгөөд эдгээрийн нэг нь Хургалжийн төрөл болно. Тус төрлийн ангилалзүйн асуудлыг шийдэхийн тулд Шинжлэх Ухааны Академийн Ботаникийн цэцэрлэгт хүрээлэнгийн Ургамлын сан (UBA) болон цахим гербарийн санд хадгалагдаж буй нийт 147 хуудас цуглуулгыг ашигласан. Монгол оронд тархан ургаж байгаа Хургалжийн (Eragrostis Wolf) төрлийн ургамалд ургал болон үржлийн эрхтэн дээрх булчирхайны байрлал, үржлийн эрхтэн дээрх үслэгийн байрлал, түрүүхэйн хэлбэр, хэмжээ, цэцгийн тоо, цэцгийн доод хайрсны хэлбэр, хэмжээ нь нэлээд тогтвортой шинж тэмдэг болно. Эдгээр шинж тэмдгийг харгалзан манай оронд Хургалжийн (Eragrostis Wolf) төрлийн Eragrostis minor Host., Eragrostis pilosa (L) Beauv., Eragrostis amurensis Probat., Eragrostis cilianensis (All.) Vignolo ex Janch гэсэн дөрвөн зүйл тархан ургана. Дээрх зүйлүүд нь навчны ирмэг дагуу болон доод гадаргуун дээрх булчирхай, түүний хэлбэр, байрлал, цэцгийн тоо, түрүүхэй, залааны үений үслэгээр өөр хоорондоо ялгарах бөгөөд үүн дээр тулгуурлан зүйл таних түлхүүрийг бичсэн. Eragrostis amurensis нь өмнөх бүртгэл бичгүүдэд огт тусгагдаагүй, бидний судалгаагаар тус зүйлийг Хөвсгөл, Хэнтий, Монгол Дагуур, Монгол -Алтай, Дундад Халх, Дорнод Монгол, Олон нуур, Дорноговийн тойргуудад, харин Eragrostis minor Хянганы уулын нугат хээрийн тойрогт, Eragrostis pilosa зүйлийг Ховдын цөлжсөн хээрийн тойрогт нэмэн бүртгэж байна. Түлхүүр үг: Хургалжийн төрөл, зүйлийн тоо, цэгэн тархалт